(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The effects of irradiation on the structure of purified multi-walled carbon nanotubes (MWCNTs) having 6-19 graphitic shells and outer diameters of 8.15-17.11 nm were investigated using electron beam of energies 200 keV and dose of 2.16 x 1017 e cm-2s-1. It was observed that the electron irradiation created a number of chronological alterations in the tube structures. These were identified to be tube contraction, destruction of the innermost graphitic shell, deformation of graphitic shells and its proliferation, break down of the graphitic shells and their spreading into the tube hole and finally the destruction of the whole tube. MWCNTs having the largest innermost diameter found suffer from the highest contraction. The tube contraction behavior found stops when the innermost graphitic shell starts to destroy. Irradiation affected the innermost graphitic shell first and that of the smallest diameter was the more rapidly. It occurred probably due to having the highest curvature value. Tubes having inner shell of diameter about 4.8 nm suffer from fractional destruction within 5-15 s of irradiation exposure. Such a shell was ruined within 1 minute of irradiation exposure but that of diameter 7.0 nm was survived up to 2 minutes. It seems that the irradiation induced defects created in the MWCNTs can be used for the diversified applications of nanotubes such as the hydrogen storage enhancement in them. Keywords: Carbon nanotube; Electron irradiation; Tube contraction; Innermost shell; Defect. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8099 Bangladesh J. Sci. Ind. Res. 46(1), 9-16, 2011